PERTEMUAN AGAMA DAN BUDAYA: Untuk Mewujudkan the Excellent of Islamic Civilization - Chamidah, Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
Thinking or ijtihad is not new in the Islamic world. However, what happens in the reality now is the opposite. The western world has dominated several aspects, such as conducting research and experimentation as a form of thinking activities, and have implemented many grand theories in various fields. Therefore, all Muslims must be aware and take action to play a role in the world. Islam is as a divine revelation from God which was revealed to Prophet Muhammad and as a guide to happiness in the world and the Hereafter. The Holy Quran contains the assertion that Islam is meant for all mankind since the Prophet Muhammad is the messenger of God to all mankind. It means that the Arabs and non-Arab nations should apply the teachings of Islam in the same level Besides, as a universal religion, Islam does not depend on a language, place, or time and human groups. Thus the use of Arabic for the Holy Qur’an is actually more of a technical problem concerning the delivery of the message rather than value problem.